2012
DOI: 10.1590/s1516-635x2012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inverting the position of layers eggs during storage on hatchery performance parameters

Abstract: Storing hatchable eggs is a common practice in commercial hatcheries. However, storage time may negative effects on several performance parameters. An experiment was carried out to evaluate inverting egg position during storage of eggs laid by young and old layer breeders. Fertile eggs of 32 and 58-week-old breeders were stored for seven, 14, and 21 days at 18ºC ± 2ºC and 80% ± 10% relative humidity (RU). The following parameters were evaluated: egg weight loss, hatchability and hatchling weight, and embryodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…In the present trial, EWL was not influenced by storage orientation. This agrees with the findings of Tiwary and Maeda (2005) that the position of eggs during storage had no effect on EWL but contrary to those of Schmidt et al (2002) and Lima et al (2012) that eggs stored with NEU had lower weight loss. The reason adduced to the lower weight loss in NEU orientation by the authors is that the traditional BEU allows for more evaporation and albumen water losses from stored eggs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present trial, EWL was not influenced by storage orientation. This agrees with the findings of Tiwary and Maeda (2005) that the position of eggs during storage had no effect on EWL but contrary to those of Schmidt et al (2002) and Lima et al (2012) that eggs stored with NEU had lower weight loss. The reason adduced to the lower weight loss in NEU orientation by the authors is that the traditional BEU allows for more evaporation and albumen water losses from stored eggs.…”
Section: Discussionsupporting
confidence: 92%
“…However,Lima et al (2012) reported an increase in hatchling weight in NEU eggs. The longer period of storage in the report ofLima et al (2012) may be the reason for the result.In conclusion, storage of TN chicken eggs up to 7 days lowered fertility and hatchability. If the HFE up to 70% is envisaged, then eggs could be stored for up to 7 days in NUE orientation but the storage should not extend beyond 3 days in BEU orientation.…”
mentioning
confidence: 93%
See 3 more Smart Citations